Precision Agriculture and Wildlife Surveillance Using IoT for Crop Protection and Health Monitoring - R., Kiruthika; G., Karthy (Journal of ISMAC, 2025)
AI and IoT in smart agriculture are revolutionizing the industry through intelligent monitoring and control. The proposed system consists of a mobile app and several smart sensors that communicate with the application over a network. The sensors continuously provide values for several important agricultural variables, such as humidity, temperature, and soil moisture. This system makes water management efficient at the click of a button by enabling farmers to operate industrial pump sets remotely and optimize irrigation. The system also employs AI-driven animal recognition technology to identify common crop-destroying animals, such as birds, goats, cows, and buffalo. The farmer is instantly alerted of the intruder and the necessity to act when a warning buzzer is triggered and a photo is sent to them. Aside from protecting crops from damage, this ingenious hands-free approach considerably reduces the need for human labor, enhancing the safety and efficiency of farming.
Keywords: Arduino Board; Soil Moisture Sensor; Temperature Sensor; Rain sensor; Node MCU; LCD; Relay